1990
DOI: 10.1242/jcs.97.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Antibody markers of basal cells in complex epithelia

Abstract: In the course of immunohistochemical studies it has become apparent that there is a distinct phenotype of keratin expression that is shared by basal epithelial cells in a variety of different tissues. A basal cell can be defined as a cell in contact with a basal lamina but with no free luminal surface; this distinguishes it from a simple epithelial cell, which has a free luminal surface as well as basal lamina contact, and from stratifying suprabasal keratinocytes, which have neither basal lamina contact nor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…Other antibodies used were as follows: mouse mAbs used were anti-K14 ( Purkis et al, 1990 ), anti-desmoplakin (11-5F) (gifted by David Garrod, The University of Manchester, Manchester, United Kingdom), anti–β-actin (clone AC-15, number A5441, Sigma-Aldrich, St. Louis, MO), anti–β-catenin (number ab16051, Abcam, Cambridge, United Kingdom; clone 14, number 610153, BD Biosciences, San Jose, CA), and anti–keratin 17 (number NCL-L-CK17, Leica Biosystems, Richmond, IL); rabbit mAbs or polyclonal antibodies used were anti–phospho-STAT1 (Tyr701) (clone D4A7, number 7649, Cell Signaling Technology, Danvers, MA), anti-STAT1 (clone D1K9Y, number 14994, Cell Signaling Technology), and anti-phospho-Histone H3 (Ser10) Antibody (clone MC463, number 04-817, Merck Millipore, Burlington, MA); secondary antibodies used were goat anti-rabbit IgG (H+L) Alexa Fluor 594 (number A-11037, Thermo Fisher Scientific); goat anti-mouse IgG (H+L) Alexa Fluor 568 (number A-11031, Thermo Fisher Scientific); Anti-Mouse IgG (H+L), HRP Conjugate (number W4021, Promega, Madison, WI); and Anti-Rabbit IgG (H+L), HRP Conjugate (number W4011, Promega); and antibody to human kappa light chain conjugated to horseradish peroxidase was used in ELISA (kindly provided by Prof PG Sveshnikov, Russian Research Center for Molecular Diagnostics and Treatment, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Other antibodies used were as follows: mouse mAbs used were anti-K14 ( Purkis et al, 1990 ), anti-desmoplakin (11-5F) (gifted by David Garrod, The University of Manchester, Manchester, United Kingdom), anti–β-actin (clone AC-15, number A5441, Sigma-Aldrich, St. Louis, MO), anti–β-catenin (number ab16051, Abcam, Cambridge, United Kingdom; clone 14, number 610153, BD Biosciences, San Jose, CA), and anti–keratin 17 (number NCL-L-CK17, Leica Biosystems, Richmond, IL); rabbit mAbs or polyclonal antibodies used were anti–phospho-STAT1 (Tyr701) (clone D4A7, number 7649, Cell Signaling Technology, Danvers, MA), anti-STAT1 (clone D1K9Y, number 14994, Cell Signaling Technology), and anti-phospho-Histone H3 (Ser10) Antibody (clone MC463, number 04-817, Merck Millipore, Burlington, MA); secondary antibodies used were goat anti-rabbit IgG (H+L) Alexa Fluor 594 (number A-11037, Thermo Fisher Scientific); goat anti-mouse IgG (H+L) Alexa Fluor 568 (number A-11031, Thermo Fisher Scientific); Anti-Mouse IgG (H+L), HRP Conjugate (number W4021, Promega, Madison, WI); and Anti-Rabbit IgG (H+L), HRP Conjugate (number W4011, Promega); and antibody to human kappa light chain conjugated to horseradish peroxidase was used in ELISA (kindly provided by Prof PG Sveshnikov, Russian Research Center for Molecular Diagnostics and Treatment, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…The following mouse monoclonal antibodies were used as primary antibodies: anti-phospho-ERK1/2 (Thr202/Tyr204) (clone E10, #9106; Cell Signaling Technologies, MA, USA), anti-β-actin (clone AC-15, #A5441; Sigma-Aldrich Corporation, MO, USA), anti-desmoplakin (clone 11-5F; gift from David Garrod, University of Manchester, UK), anti-keratin 14 (clone LL001; Purkis et al, 1990 ), anti-keratin 10 (clone DE-K10, #M7002; Agilent Technologies, CA, USA), anti-E-cadherin (clone 36, #610182; BD Biosciences, CA, USA) and anti-Ki-67 (clone MM1, #NCL-L-Ki67-MM1; Leica Biosystems, IL, USA). The following rabbit monoclonal or polyclonal antibodies were also used as primary antibodies: anti-phospho-AKT (Ser473) (clone D9E, #4060), anti-AKT (clone C67E7, #4691), anti-phospho-ERK1/2 (Thr202/Tyr204) (clone D13.14.4E, #4370), anti-ERK1/2 (clone 137F5, #4695) and anti-YAP (clone D8H1X, #14074) were purchased from Cell Signaling Technologies (MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Basal cells are epithelial progenitor cells and are defined by the expression of transformation-related protein (TP63) and cytokeratins 5 and 14 (KRT5/14) ( 29 , 30 ). Beside these classical markers, Zhao et al demonstrated that YES-associated protein 1 (YAP) is essential for the maintenance of airway basal cell identity and that YAP is closely related to TP63 to regulate stem cardinal behavior and to help determine epithelial architecture ( 31 ).…”
Section: Basal Cell Phenotypesmentioning
confidence: 99%